An Autologous Protein Solution prepared from the blood of osteoarthritic patients contains an enhanced profile of anti-inflammatory cytokines and anabolic growth factors - O'Shaughnessey, Krista (2014)
The objective of this clinical study was to test if blood from osteoarthritis (OA) patients (n = 105) could be processed by a device system to form an autologous protein solution (APS) with preferentially increased concentrations of anti-inflammatory cytokines compared to inflammatory cytokines. To address this objective, APS was prepared from patients exhibiting radiographic evidence of knee OA. Patient metrics were collected including: demographic information, medical history, medication records, and Knee Injury and Osteoarthritis Outcome Score (KOOS) surveys. Cytokine and growth factor concentrations in whole blood and APS were measured using enzyme-linked immunosorbent assays. Statistical analyses were used to identify relationships between OA patient metrics and cytokines. The results of this study indicated that anti-inflammatory cytokines were preferentially increased compared to inflammatory cytokines in APS from 98% of OA patients. APS contained high concentrations of anti-inflammatory proteins including 39,000 ± 20,000 pg/ml IL-1ra, 21,000 ± 5,000 pg/ml sIL-1RII, 2,100 ± 570 pg/ml sTNF-RI, and 4,200 ± 1,500 pg/ml sTNF-RII. Analysis of the 82 patient metrics indicated that no single patient metric was strongly correlated (R(2) > .7) with the key cytokine concentrations in APS. Therefore, APS can be prepared from a broad range of OA patients.